2021
DOI: 10.5812/asjsm.106582
|View full text |Cite
|
Sign up to set email alerts
|

Immune Function Response Following a Low-carbohydrate, High-fat Diet (LCHFD) in Patients with Type 2 Diabetes

Abstract: Background: Type 2 diabetes is a chronic metabolic disorder that can result in micro- and macrovascular complications and is complicated by an impaired healing process. Research suggests that both dietary factors and habitual physical activity influence the hemostatic system through several pathways. Objectives: The study attempted to investigate if a low-carbohydrate, high-fat diet (LCHFD), on its own or in conjunction with physical activity, could alter hematologic variables in patients with type 2 diabetes.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 54 publications
0
2
0
Order By: Relevance
“…Fifteen studies presented equivocal results (62,87,90,92,96,100,110,112,114,123,128,132,135,138,140) (no significant change in inflammatory markers), two reported mixed results (51,124) and two studies reported negative results (105,121) (increased inflammatory markers). Total energy intake was similar to the neurological outcomes group; thirty-eight were ad libitum/ weight maintenance studies, fifteen had mild-to-moderate calorie restriction (91,92,(105)(106)(107)(108)(109)111,116,125,127,129,132,134) , seven were very low-calorie (<800 kcal per day) (57,93,97,102,112,115,120) and three used mixed models (51,94,101) .…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Fifteen studies presented equivocal results (62,87,90,92,96,100,110,112,114,123,128,132,135,138,140) (no significant change in inflammatory markers), two reported mixed results (51,124) and two studies reported negative results (105,121) (increased inflammatory markers). Total energy intake was similar to the neurological outcomes group; thirty-eight were ad libitum/ weight maintenance studies, fifteen had mild-to-moderate calorie restriction (91,92,(105)(106)(107)(108)(109)111,116,125,127,129,132,134) , seven were very low-calorie (<800 kcal per day) (57,93,97,102,112,115,120) and three used mixed models (51,94,101) .…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
“…Total energy intake was similar to the neurological outcomes group; thirty-eight were ad libitum/ weight maintenance studies, fifteen had mild-to-moderate calorie restriction (91,92,(105)(106)(107)(108)(109)111,116,125,127,129,132,134) , seven were very low-calorie (<800 kcal per day) (57,93,97,102,112,115,120) and three used mixed models (51,94,101) . Fifty-seven studies reported weight loss, two reported no weight loss (98,114) and four did not report a finding (83,90,134,139) . Overall, a total of 2296 participants commenced an LCD or KD trial that reported an inflammatory outcome.…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%